Penerapan Kriteria Reesi Sebagai Assessment Tools Monitoring Dan Evaluasi Perencanaan Pembangunan Daerah di Indonesia - Taufik Hidayat (Balitbangda Provinsi Lampung, 2017)
To ensure the implementation of regional development planning in accordance with the objectives and targets that have been determined it was important to conduct monitoring and evaluation activities. The application of REESI criteria as assessment tools in monitoring and evaluation was expected to better ensure the success of planning in every activity to be implemented. REESI stood for Relevance, Effectiveness, Efficiency, Suistainable and Impact. The method used in this research was qualitative research method. Qualitative method used in term of explorative descriptive approach.